2008
DOI: 10.1159/000127836
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Voice Handicap Index by Assessing Equivalence of European Translations

Abstract: Objective: We aimed to assess the equivalence of translations of the Voice Handicap Index (VHI). Patients and Methods: Confirmatory factor analysis was used to assess equivalence of the US version and several translations including (1) Dutch, (2) Flemish Dutch (Belgium), (3) UK English, (4) French, (5) German, (6) Italian, (7) Portuguese and (8) Swedish. VHI questionnaires were gathered from 1,281 subjects. Patients were classified into 11 voice lesion categories. Patients with incomplete response (4%) and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 19 publications
10
59
0
2
Order By: Relevance
“…The VHI, and the VHI-T 19 (the VHI with a subscale on throat problems [41], have been shown to separate subjects with and without voice disorders [41,42,66]. It is noteworthy that the highest OR of the VHI-T subscales was found on the emotional subscale, which indicates that teachers with voice problems are twice as likely as their voice healthy colleagues to score high on this subscale.…”
Section: Subjects' Assessment Of Voice Handicap and Voice Functionmentioning
confidence: 99%
“…The VHI, and the VHI-T 19 (the VHI with a subscale on throat problems [41], have been shown to separate subjects with and without voice disorders [41,42,66]. It is noteworthy that the highest OR of the VHI-T subscales was found on the emotional subscale, which indicates that teachers with voice problems are twice as likely as their voice healthy colleagues to score high on this subscale.…”
Section: Subjects' Assessment Of Voice Handicap and Voice Functionmentioning
confidence: 99%
“…9 The VHI has been translated and validated into several languages, including Dutch, and the various versions are proven to be equivalent. 10 …”
Section: Voice Handicap Indexmentioning
confidence: 99%
“…Furthermore, the Agency for Health Care Research and Quality reported in 2002 that the VHI met stringent criteria for reliability, validity and availability of normative data [10]. The VHI has been translated into many different languages [11,12,13,14,15,16,17], and it has been validated by assessing equivalence of the European translation of the questionnaire to German, French, Dutch, Italian, Portuguese, Belgian and Swedish [17]. The US VHI and the various European translations appear to be equivalent, suggesting that the results from the various published translations are comparable [17].…”
Section: Introductionmentioning
confidence: 99%
“…The VHI has been translated into many different languages [11,12,13,14,15,16,17], and it has been validated by assessing equivalence of the European translation of the questionnaire to German, French, Dutch, Italian, Portuguese, Belgian and Swedish [17]. The US VHI and the various European translations appear to be equivalent, suggesting that the results from the various published translations are comparable [17]. Current non-European translations include Brazilian Portuguese [11], Chinese [13] and Arabic [14].…”
Section: Introductionmentioning
confidence: 99%